Does a history of youth sport-related knee injury still impact accelerometer-measured levels of physical activity after 3–12 years?. (May 2022) - Toomey, Clodagh M.; Whittaker, Jackie L.; Doyle-Baker, Patricia K.; Emery, Carolyn A.
Abstract: Objectives: To examine accelerometer-measured physical activity (PA) in individuals with a knee injury history and controls and the association of moderate to vigorous PA (MVPA) with self-reported and performance measures of knee function. Design: Historical cohort. Participants: Participants with a 3–12 year history of youth sport-related knee injury and matched controls. Main outcome measures: MVPA (Actigraph GT3x-BT), Knee Injury and Osteoarthritis Outcome Score (KOOS), Triple Single-Leg Hop, Y-Balance and isometric knee strength was measured. Regression analyses examined differences in PA and the association between MVPA and knee function, adjusted for injury history, sex and time since injury. Results: Participants (42 injured, 43 controls) had a median age of 23.4 (range 16–29) years. The previously injured group spent less daily adjusted minutes in MVPA [-13.5 (95% CI -25.6, −1.4)] than controls, and females had 10.8 min (95% CI -20.2, −1.4) less MVPA than males. Higher MVPA was associated with better KOOS sport and recreation [β = 0.05, 95% CI (0.01, 0.09)] adjusted for injury history. No other associations were observed. Conclusion: Previously injured youth participated in less MVPA compared to controls 3–12 years later. Lower MVPA is associated with poorer self-reported sport and recreation knee function which may have long-term negative health consequences. Highlights: Youth with a 3–12-year knee injury history participate in less MVPA than controls. Regardless of history of knee injury, females participate in less MVPA than males. Low MVPA was associated with poor self-reported knee function during sport/recreation.